1981
DOI: 10.1007/bf01657832
|View full text |Cite
|
Sign up to set email alerts
|

TSH suppression in the management of thyroid nodules and thyroid cancer

Abstract: Clinical and experimental data concerning TSH suppression, by giving exogenous thyroid hormone, in patients with goiter and in patients with thyroid cancer show a beneficial effect. In the goiter patients, TSH suppressive therapy seems most effective in young patients with diffuse or newly discovered goiters, in hypothyroid patients, and in patients with chronic lymphocytic thyroiditis or compensatory thyroid hypertrophy after partial thyroidectomy. With TSH suppressive therapy about 2/3 of thyroid nodules bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
3

Year Published

1985
1985
2008
2008

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 44 publications
1
41
0
3
Order By: Relevance
“…Das Belassen dieser wachstumsstimulierbaren Knoten im Schilddrüsenrestparenchym kann im weiteren Verlauf unabhängig von der TSH-Stimulation oder dem intrathyreoidalen Jodangebot zur Entwicklung einer Rezidivstruma führen. Dies bedeutet, dass selbst durch eine L-Thyroxin und/oder Jodsubstitution das Knotenwachstum und damit das Auftreten von Rezidivstrumen nicht immer vermeidbar ist [1,3,4,9,12,15,16,18,40]. In der Literatur werden Rezidivraten nach subtotaler Schilddrüsenresektion trotz medikamentöser Rezidivprophylaxe von über 40% angegeben [31].…”
Section: Struma Benigna · Totale Thyreoidektomie · Chirurgie · Kompliunclassified
See 1 more Smart Citation
“…Das Belassen dieser wachstumsstimulierbaren Knoten im Schilddrüsenrestparenchym kann im weiteren Verlauf unabhängig von der TSH-Stimulation oder dem intrathyreoidalen Jodangebot zur Entwicklung einer Rezidivstruma führen. Dies bedeutet, dass selbst durch eine L-Thyroxin und/oder Jodsubstitution das Knotenwachstum und damit das Auftreten von Rezidivstrumen nicht immer vermeidbar ist [1,3,4,9,12,15,16,18,40]. In der Literatur werden Rezidivraten nach subtotaler Schilddrüsenresektion trotz medikamentöser Rezidivprophylaxe von über 40% angegeben [31].…”
Section: Struma Benigna · Totale Thyreoidektomie · Chirurgie · Kompliunclassified
“…Rojdmak und Jarhult [31] berichteten über eine Rezidivrate von 42% nach subtotaler Resektion bei multinodulärer Knotenstruma. Andere Autoren berichten über ähnliche Rezidivraten, wobei die Inzidenz der Rezidivstruma nach postoperativer medikamentöser Prophylaxe mit L-Thyroxin zwischen 0% und 14,5%, ohne medikamentöse Rezidivprophylaxe zwischen 10,7% und 43% lag [1,4,12,26]. Der direkte Zusammenhang zwischen einer TSHsuppressiven Schilddrüsenhormonsubstitution und der Minderung der Rezidivrate wird jedoch von vielen Autoren nicht geteilt [2,12,14,18,44].Aufgrund der Pathophysiologie der Rezidivstruma gilt die Jodsubstitution zur Rezidivprophylaxe in Jodmangelgebieten seit gut 20 Jahren als allgemein anerkannt [10,19,20,28,33].Andere Arbeitsgruppen [14] führten die Strumarezidive auf die Produktion von "insulin-like growth factor" (IGF-1) und "epidermal growth factor" (EGF) des verbliebenen Schilddrüsenrestes zurück.…”
Section: Diskussionunclassified
“…• Some clinicians might recommend treating patients with recurrent thyroid cancer of follicular cell origin with 131 I or external radiation [22][23][24]. We and others recommend surgical removal of discrete local or distant metastases to lung and bone when it can be done safely [25-28•].…”
Section: Surgerymentioning
confidence: 99%
“…Although no randomized trials of thyrotropin suppressive therapy as an adjunct to surgery have been conducted, Mazzaferri and Jhiang 5 and others 28 showed a beneficial effect of such treatment. However, Cady et al 29 reported that the administration of thyroid hormone for differentiated thyroid cancer to suppress thyrotropin did not improve survival time.…”
Section: Commentmentioning
confidence: 99%